Alcohol myopia and goal commitment - Sevincer, A. T.; Oettingen, Gabriele (Frontiers in Psychology, 2014)
According to alcohol-myopia theory, acute alcohol consumption leads people to disproportionally focus on the salient rather than the peripheral aspects of a situation. We summarize various studies exploring how myopic processes resulting from acute alcohol intake affect goal commitment. After consuming alcohol student participants felt strongly committed to an important personal goal even though they had low expectations of successfully attaining the goal. However, once intoxicated participants were sober again (i.e., not myopic anymore) they failed to act on their goal commitment. In line with alcohol-myopia theory, strong goal commitment as a result of alcohol intake was mediated by intoxicated (vs. sober) participants disproportionally focusing on the desirability rather than the feasibility of their goal. Further supporting alcohol-myopia theory, when the low feasibility of attaining a particular goal was experimentally made salient (either explicitly or implicitly by subliminal priming), intoxicated participants felt less committed than those who consumed a placebo. We discuss these effects of acute alcohol intake in the context of research on the effects of chronic alcohol consumption on goal commitment.